NATURALIZATION IN TRANSLATION OF ENGLISH ACCOUNTING TERMS INTO INDONESIAN - Anita . Basrah; Anni Holila Pulungan; Rahmad . Husein (Universitas Negeri Medan, 2021)
This research was to analyze the process of spelling adjustment of naturalization applied in translation of English accounting terms into Indonesian. The objective of the study was to find out the Process of spelling adjustment of naturalization were used by accounting terms. This research used a descriptive and qualitative method. The data of this study were words containing naturalization were taken from the translation of selected articles of accounting textbook, Accounting 21e (2008). The data were collected through documentary technique. The data analysis was concerned of the implementation of spelling adjustment of naturalization. The findings show that naturalization in English-Indonesian accounting terms occurred in three categories, namely grapheme, and syllabic adapatation (double consonant become single consonant and consonant inhibitory. The products of naturalization have followed the guidance yet several new adjustment standards need to be included to enrich the pattern of foreign term adoption. In addition, this study recommends that proess of absorption in the Indonesian guidance of term formation needs to be revisited in order to precisely classify how foreign terms spelling adjustment is made in the Indonesian language Keywords: Naturalization, Translation Procedure, Accounting Terms, Spelling Adjustment